Citizen 2.0: Transformasi Dan Tantangan Partisipasi Politik Warga Di Era Dominasi Media Sosial - Sarinah, Sarinah; Sultrayansa, Sultrayansa (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to analyze the transformation of citizen political participation in the era of social media dominance, highlighting the opportunities and challenges that arise. The Citizen 2.0 phenomenon shows a significant shift from conventional political participation to faster, more massive, and more participatory digital engagement. Social media has become a new democratic space that allows citizens to not only be consumers but also producers of political narratives. This study employs a descriptive-exploratory qualitative approach methods in Kendari City, focusing on the experiences of young, digitally active citizens. The research findings indicate that social media expands political participation access for marginalized groups and strengthens real-time citizen advocacy. However, disinformation, polarization, slacktivism, and digital inequality remain major challenges in achieving healthy digital political participation. This study proposes the need for a constructive model of digital political participation based on principles of modern public administration such as inclusivity, transparency, and responsiveness. These findings contribute to the development of literature on e-participation, digital citizenship, and smart governance, while also serving as a practical reference for governments in developing digital-based participatory policies.